Moment Analysis and translanguaging space: Discursive construction of identities by multilingual Chinese youth in Britain - Wei, Li (Journal of pragmatics, 2011)
Translanguaging is both going between different linguistic structures and systems and going beyond them. It includes the full range of linguistic performances of multilingual language users for purposes that transcend the combination of structures, the alternation between systems, the transmission of information and the representation of values, identities and relationships. Translanguaing space is a space for the act of translanguaging as well as a space created through translanguaging. It is a space where the process of what Bhabha calls “cultural translation” between traditions takes place. The notion of translanguaging space embraces the concepts of creativity and criticality, which are fundamental but hitherto under-explored dimensions of multilingual practices. Using a combination of observation of multilingual practices and metalanguage commentaries by three Chinese youths in Britain, the article retells their experiences of growing up in a society which is dominated by a variety of monolingual ideologies, their multilingual practices and the creativity and criticality shown through such practices, the identity positions they construct and present for themselves, and the social spaces they create and occupy within the wider space they find themselves in. It examines the following themes: fun with words, from weekend bilingualism to flexible multilingualism, creating space and cultivating relationships, and transnational space. In examining these themes, a method, called Moment Analysis, is proposed, which aims to capture what appears to be spur-of-the-moment actions that are semiotically highly significant to the actors and their subsequent actions, what prompted such actions and the consequences of such moments including the reactions by other people.